2015
DOI: 10.1136/jclinpath-2014-202754
|View full text |Cite
|
Sign up to set email alerts
|

Mutation detection in formalin-fixed prostate cancer biopsies taken at the time of diagnosis using next-generation DNA sequencing

Abstract: Using the methods presented here, NGS technologies can be used to screen a high proportion of patients with prostate cancer for mutations in cancer-related genes in tissue samples opening up its general use in the context of clinical trials or routine diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 31 publications
1
13
0
Order By: Relevance
“…Manson-Bahr et al showed that DNA from cancer material dissected from transrectal ultrasound needle-core biopsy specimens can be analyzed 15. The authors observed a pattern of mutation consistent with those previously observed in PC surgical tissues, including TMPRSS2 – ERG fusion and mutations in SPOP , TP53 , ATM , and MEN1 , while nonsense mutations were observed in the MAP2K5 and the NCOR2 genes.…”
Section: Ngs Analysis For Solid Cancer Diagnosissupporting
confidence: 57%
See 1 more Smart Citation
“…Manson-Bahr et al showed that DNA from cancer material dissected from transrectal ultrasound needle-core biopsy specimens can be analyzed 15. The authors observed a pattern of mutation consistent with those previously observed in PC surgical tissues, including TMPRSS2 – ERG fusion and mutations in SPOP , TP53 , ATM , and MEN1 , while nonsense mutations were observed in the MAP2K5 and the NCOR2 genes.…”
Section: Ngs Analysis For Solid Cancer Diagnosissupporting
confidence: 57%
“…Two studies have evidenced the possibility for huge screening of PC patients in routine diagnosis 15,16. Manson-Bahr et al showed that DNA from cancer material dissected from transrectal ultrasound needle-core biopsy specimens can be analyzed 15.…”
Section: Ngs Analysis For Solid Cancer Diagnosismentioning
confidence: 99%
“…Intra-individual metastases, however, might undergo a monoclonal selection process attributable to aggressive treatments, which would account for the inconsistency between this and other reports documenting a multiclonal seeding process resulting in intra-individual molecular heterogeneity either in primary prostate tumours 114 or metastases 126 . Despite these challenges, new developments in applied techniques (such as genomic and/or transcriptional profiling of AR signatures) and lineage markers might enable the advancement of clinical characterization of lineage crises because they can be used in clinical settings to evaluate treatment-induced lineage crises in formalin-fixed, paraffin-embedded primary or metastatic tumour samples 74,127 and even in urine samples 27 . Increasingly sensitive assays can also be used to screen for the presence of neuroendocrine or EMT-like cells in patient blood samples 28 , thereby enabling more frequent sampling than many other sampling techniques.…”
Section: Treatment-induced Prostate Lineagesmentioning
confidence: 99%
“…However, tissue from small diagnostic samples have demonstrated their utility for providing MPS starting material. Ninety‐four per cent of prostate core biopsies (FFPE) yielded sufficient DNA for MPS analysis of 365 cancer‐related genes, and FNA smears and cellblocks have also been used to provide sufficient DNA yield . FNA samples [e.g.…”
Section: Clinical Genomics In Pathology Practicementioning
confidence: 99%